Analysis of the Microbial Landscape of Infection Site and the Effectiveness of Antibiotic and Immunotherapy in Patients with Diabetic Foot - V. I. Sokolova; D. A. Sychev; E. I. Vasilieva; M. B. Babarina; L. I. Zavolovskaya (Антибиотики и Химиотерапия)
The article analyses the results of the study of 169 strains of microorganisms obtained from wound discharge from 132 patients with diabetes mellitus. Staphylococcus spp. bacteria held a leading place among Gram-positive pathogens. Gram-negative pathogens — Escherichia coli, Pseudomonas aeruginosa, etc. — were found less frequently. All isolated cultures were sensitive to levofloxacin and moxifloxacin, and only Acinetobacter spp. (n=2) remained intact (in vitro) after the use of levofloxacin. The intra-arterial route of administration of levofloxacin (500 mg/day) in combination with polyoxidonium (12 mg/day) through a port was used in 16 patients with diabetic foot. In all clinical cases, positive dynamics was noted: subsiding of the inflammatory process, cleansing of the wound from a purulent-necrotic substrate, and early epithelialization of the wound was observed in patients with diabetic foot.